Estimation of invasive pneumococcal disease dynamics parameters and the impact of conjugate vaccination in Australia - Karyn L. Sutton; H.T. Banks; Carlos Castillo-Chávez (Mathematical Biosciences and Engineering)
Pneumococcal diseases, or infections from the etiological agent Streptococcus pneumoniae, have long been a major cause of morbidity andmortality worldwide. Recent advances in the development of vaccines for theseinfections have raised questions concerning their widespread and/or long-termuse. In this work, we use surveillance data collected by the Australian NationalNotifiable Diseases Surveillance system to estimate parameters in a mathemat-ical model of pneumococcal infection dynamics in a population with partialvaccination. The parameters obtained are of particular interest as they are nottypically available in reported literature or measurable. The calibrated modelis then used to assess the impact of the recent federally funded program thatprovides pneumococcal vaccines to large risk groups. The results presentedhere suggest the state of these infections may be changing in response to theprograms, and warrants close quantitative monitoring.